2012
DOI: 10.1007/s00268-012-1888-2
|View full text |Cite
|
Sign up to set email alerts
|

Medial Versus Lateral Approach in Laparoscopic Colorectal Resection: A Systematic Review and Meta‐analysis

Abstract: Compared with the lateral approach, the medial approach has the advantages of shorter operative time and possibly lower conversion rate; it also can be as safe as the lateral approach. Whether the MA has less blood loss and lower hospitalization costs remains to be confirmed, and its oncological safety and long-term prognosis are not clear. Due to insufficient data from a limited number of studies, inadequate assessment of the results may arise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In all cancer cases, a medial to lateral approach with high vessel ligation was used [24]. In 11/13 female patients, the specimen was extracted though a colpotomy, while in the remaining two cases, a supra-pubic mini-laparotomy was used.…”
Section: Resultsmentioning
confidence: 99%
“…In all cancer cases, a medial to lateral approach with high vessel ligation was used [24]. In 11/13 female patients, the specimen was extracted though a colpotomy, while in the remaining two cases, a supra-pubic mini-laparotomy was used.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 A meta-analysis by Ding et al, 2013 has analysed 5 cohort studies including 2 randomized control trials and 3 retrospective studies incorporating 881 patients. 10 They reported significantly shorter operative time. Right-sided resections took 136 (114-145) minutes in the medial-tolateral group compared to 156 (136-157) minutes in the lateral-to-medial.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, numerous studied explored different surgical approaches and tried to find a better one. Jie Ding et al shown that the medial approach is a preferable approach at present [21] .…”
Section: Discussionmentioning
confidence: 99%